Effects of technology-integrated chemistry instruction on students’ academic achievement and retention capacity - Derejaw Yesgat; Solomon Melesse; Dereje Andargie; Belete Bedemo Beyene (Journal of Education and Learning (EduLearn), 2023)
This study determined how chemistry instruction using technology affected student achievement and retention. To achieve the goal of the study, Solomon’s four-group quasi-experimental research design was used. The one-way analysis of variance (ANOVA) and independent sample t-test were used to statistically examine the data. A one-way ANOVA analysis revealed that, for achievement and retention, respectively, the mean scores of both trial groups showed statistically significant differences from the mean scores of comparison groups F (3.161)=88.568, p0.05 and F (3.161)=14.75, p0.05). The independent samples t-test on the achievement and retention post-test mean score of the experimental and comparison groups respectively, was statistically significant (t (163)=16.05, p0.05 and t (162.09)=7.61, p0.05). Independent sample t-test shows that male and female students’ post-test scores for achievement or retention in the experimental group results was (t (42)=1.53; p0.05 and t (38)=-0.465; p0.05, respectively. This intervention has no statistically significant gender related impact on students’ achievement and retention. Thus, it is conceivable to draw the conclusion that chemistry instruction that incorporates technology enhances student achievement and retention, but its effect is gender neutral. According to recent studies, chemistry teachers and teacher training programs should use technology-integrated lessons to help students acquire and recall chemical bonding concepts.